Strategi Internalisasi Nilai Akhlak Berbasis Kitab Akhlaq Lil Banin di Lembaga Pendidikan Islam Non Formal: Strategy of Moral Values Internalization Based on The Book of Akhlaq Lil Banin at Non-Formal Islamic Educational Institutions - Muhamad Alwi Aziz; Imam Makruf (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to analyze the implementation of moral education and its impact on the behavioral development of students at PTQ Haidar al‑Hidayah. The research employed a descriptive qualitative approach, utilizing observations, interviews, and documentation to collect data on institutional understanding, strategies for internalizing moral values, and their effects on student behavior. The findings indicate that the institution demonstrates a strong understanding and commitment to moral education, implemented through the integration of ethical values into the Qur’an memorization program, habituation of noble character (akhlaqul karimah), instruction based on the Akhlaq lil Banin text, and religious as well as social extracurricular activities. Strategies for internalizing moral values combine lectures, storytelling, exemplary modeling (uswah hasanah), and habituation (ta’dib wa ta’wid), enabling students to cognitively understand, emotionally internalize, and practically apply moral values in their daily lives. The study observed significant improvements in politeness, discipline, responsibility, honesty, and respect for teachers. These results confirm that a holistic and integrated moral education effectively fosters sustainable moral behavior among students. The findings can serve as a model for other Islamic educational institutions seeking to develop character education programs grounded in moral values and practical experiences.